EXPLORATION OF CHARACTER EDUCATION VALUES IN ES IST ALLES EITEL POETRY BY ANDREAS GRYPHIUS - Lendo, Sjuul; Samola, Nurmin F (Journal of English Language and Literature Teaching, 2022)
This study aims to describe the values of character education contained in the poem Es ist Alle Eitel, the work of a German writer named Andreas Gryphius. This study uses a qualitative approach with content analysis method based on semiotic analysis, in this case semiotic analysis based on the semiotic theory of Charles Sanders Pierce. The results of the analysis show that in this poem there are semiotic signs in the form of indexes and symbols, which reflect the values of character education. The index sign is found more than the symbol sign. While the icon sign is not found in this poem. Furthermore, the character education values contained in this poem are the character of believing and loving God, sincere faithful, humble, empathetic, intelligent responsibility and love for the environment.